INTEGRASI PENDIDIKAN KARAKTER DALAM KURIKULUM OUTCOME-BASED EDUCATION (OBE) STRATEGI DAN IMPLEMENTASI EFEKTIF - Inka Widiarti; Susi Puspita Sari; Jamal Mirdad; Unan Yusmaniar Oktiawati; M. Amin; Hilmi (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
Character education has a very important role in shaping students' moral and ethical values, especially in facing the demands of 21st century education. This study aims to examine the integration of character education in Outcome-Based Education (OBE)-based curriculum by emphasizing effective strategies and implementation. Using a qualitative approach, this study identifies key components of character education that are in line with OBE principles, such as outcome orientation, student-centered learning, and development of measurable competencies. It also reviews best practices, including curriculum design, teaching methods and evaluation techniques that support learners' holistic development. The results show that good integration of character education in the OBE curriculum not only supports academic success, but also enhances learners' social responsibility and moral integrity. This article provides practical insights and recommendations for educators, policy makers and institutions in effectively implementing character education within the OBE framework.